Compliance to code of ethics : a mixed method study on the Malaysian accounting profession / Sharifah Khadijah Syed Agil - Syed Agil, Sharifah Khadijah (2010)
The phenomenon of global and national corporate collapse due to ethical malpractices, the evidence of mixed findings on the usefulness and effectiveness of code in prior studies and the incidents of anomaly with respect to compliance to codes of ethics by professional accountants underpinned this research on professional accountants' behavioral intention to comply with a codes of ethics. This three-phased study adopts a socio-psychological perspective on Malaysian professional accountants' compliance to the By-Laws of the Malaysian Institute of Accountant (MIABL) (revised 2007). This is achieved by identifying the determinants of compliance behaviour and factors affecting these determinants based on Ajzen's (1988) Theory of Planned Behaviour (TPB) which provides the "skeletal proposition" in understanding such behaviour. The robustnesses of the mixed method approach employed in this study demonstrated inherent and internal consistency of findings from different sources or methods. Findings and analysis of content analysis conducted in phase one revealed code of ethics that is "public practice" in focus, and "designation specific" and "individual specific", which found strong support from the Experts survey undertaken in phase two of the study. Variability in behavioural intention towards MIABL compliance was discovered in the in-depth interviews conducted in phase three of the study. The variability that exists within and between categories of practice in the accountancy profession in Malaysia reflects importance of structures and landscapes on the basis of political economy theory.